THE POETIC FEATURES OF THE NATURE OF CHARACTERS IN OLMAS UMARBEKOV’S SHORT STORIES - Yangiboyeva , Sohiba (Педагогика и психология в современном мире: теоретические и практические исследования, 2026)
In this article Nazira from "Sweet Evenings" by Olmas Umarbekov, Mavluda from "Abdulla qovunchi", Zumrad from "Nomus", Aunt Sarvi from "Kuz havosi", Gozal from " Gul sotuvchi qiz ", "Oyning oltin o‘rog‘i" . Characters like Iroda in Rogi and Solihabibi in Yer yonganda are given a unique character and emotional experiences of a woman in the plot of the story.